Pengelolaan Lansekap Desa Budaya Kertalangu Kecamatan Denpasar Timur Kota Denpasar Provinsi Bali - ANGGAR RETNO ULUPI; COKORDA GEDE ALIT SEMARAJAYA; NI NYOMAN ARI MAYADEWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Landscape Management in Desa Budaya Kertalangu Kecamatan Denpasar Timur Kota Denpasar Provinsi Bali Desa Budaya Kertalangu (DBK) located in By Pass Ngurah Rai No. 88X street. The place is near Sanur and not so far from Gianyar. DBK is one of the pilot project from the Local Government as a tourism cultural model, the concept is blend of agricultural activities and cultural arts. The purpose of this research are to determine the applicable of DBK management, to  analyzed the factors of affect the landscape maintenance activities. This research are consider internal and external of DBK, starting from observation, identification the type of the plants and continued by interview with compatible persons, get literature and distribute questionnaires to determine the visitors perceptions about DBK. The research indicated that it was still bad management standard level. This can be seen from the internal management is not going well from the employees, owners and the gardeners. The bad maintenance will be unsatisfied of the visitors on DBK. Key word: management and maintenance garden